2016
DOI: 10.1038/ncomms12564
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensing by the α6-integrin confers an invasive fibroblast phenotype and mediates lung fibrosis

Abstract: Matrix stiffening is a prominent feature of pulmonary fibrosis. In this study, we demonstrate that matrix stiffness regulates the ability of fibrotic lung myofibroblasts to invade the basement membrane (BM). We identify α6-integrin as a mechanosensing integrin subunit that mediates matrix stiffness-regulated myofibroblast invasion. Increasing α6-expression, specifically the B isoform (α6B), couples β1-integrin to mediate MMP-2-dependent pericellular proteolysis of BM collagen IV, leading to myofibroblast invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 66 publications
(85 reference statements)
1
92
0
1
Order By: Relevance
“…Podosomes or invadopodia lead invading fibroblasts with activation of cell surface proteases and remodeling of the ECM (12,27,28). A recent study from our group demonstrated that mechanosensing of stiffened matrix by β 6 integrins confers an invasive phenotype of IPF lung myofibroblasts and mediates experimental lung fibrosis (29). IPF is also characterized by basement membrane destruction, which allows fibroblasts to invade into the provisional matrices that develop in alveoli after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Podosomes or invadopodia lead invading fibroblasts with activation of cell surface proteases and remodeling of the ECM (12,27,28). A recent study from our group demonstrated that mechanosensing of stiffened matrix by β 6 integrins confers an invasive phenotype of IPF lung myofibroblasts and mediates experimental lung fibrosis (29). IPF is also characterized by basement membrane destruction, which allows fibroblasts to invade into the provisional matrices that develop in alveoli after injury.…”
Section: Discussionmentioning
confidence: 99%
“…As two examples, the expression of integrins α 2 , α 3 , and β 1 is higher in mouse mammary epithelial cells cultured on TCPS compared to cells on a soft basement membrane-like matrix [50], and integrin α 5 expression was found to increase 5-fold on a 10 kPa stiffness compared to 1 kPa in cancer cells [17] and over a similar range in fibroblasts [63]. Most of this work has focused on collagen-and fibronectin-binding integrins, with the exception of one paper on integrin α 6 in fibroblasts, where expression increased with stiffness, resulting in increased invasion [64]. We demonstrate here the mechanosensitivity of integrin α 6 in breast cancer cells, and the downstream regulation of cell adhesion, migration, and response to EGF (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, activation of protease-activated receptor (PAR)-2 by thrombin suppresses TRPV4 activity in macrophages and resolves lung injury (74). Similarly, PARs are also activated by neutrophil elastase (NE), matrix metalloproteases (MMPs) or other microbial proteases (33,(75)(76)(77)(78)(79) which has been implicated to degrade ECM and thereby causing remodeling and matrix stiffening during infection (33,63,73,80).…”
Section: Trpv4 In Host Defensementioning
confidence: 99%